Double trouble in a patient with myotonia. (14th February 2013) - Hehir, Michael K; Logigian, Eric; Raja Rayan, Dipa L; Ciafaloni, Emma
Abstract : Non-dystrophic myotonias (NDM) are characterised by muscle stiffness during voluntary movement owing to delayed skeletal muscle relaxation caused by mutations in the chloride (CLCN1) and sodium (SCN4A) skeletal muscle channel genes. Late onset acid maltase deficiency (AMD) is characterised by progressive respiratory and proximal muscle weakness; electrical but not clinical myotonia can be observed. Case report of a unique patient with concurrent NDM and AMD. We describe the clinical presentation and management of a patient with two rare neuromuscular disorders. This case illustrates the importance of reopening the differential diagnosis in patients who do not conform to the typical natural history of a specific disease.